PENERAPAN HIDS (HOST INTRUSION DETECTION SYSTEM) DALAM MEMBANGUN KONFIGURASI FIREWALL SECARA DINAMIK - Alfian Firdaus; Haruno Sajati; Yuliani Indrianingsih (Compiler, 2013)
Development o f information technology and computer networks in particular its services on the one hand facilitate the work of human beings, but as the very widespread use of the internet, the security level of digital data has become more vulnerable to exploitation. The problem arises when the attacks happened on a computer network in a relatively fast, so that an administrator must always keep an eye on the computer network security. Limitations o f an administrator is exactly what underlies thecreation o f a system capable o f detecting and prevention of these attacks, so the time efficiency can be actually implemented. The system is built to prevent attacks on computer networks such as port scanning, ftp, ssh and telnet brute force. This system will analyze the number o f errors that occur on login these services, and makes a decision system if the login error exceeds the tolerance of an administrator. I f the number o f errors exceeds the tolerance, it will automatically create the firewall rules in a very short duration is one minute, so the system is able to prevent the attacks which happened in a very quick time.